Long‐term suppression of EAE relapses by pharmacological impairment of epitope spreading. (March 2014) - Cavone, L; Peruzzi, B; Caporale, R; Chiarugi, A
<x xml:space="preserve">Abstract</x> Background and Purpose Immune events sustaining dendritic cell (DC)‐dependent epitope spreading (ES) are of key relevance to the development of relapses during multiple sclerosis (MS). Although no drugs are currently available to target ES, its inhibition would represent a major advancement in MS therapy. Inhibitors of the enzyme PARP‐1 afford protection in animal models of MS, such as experimental autoimmune encephalomyelitis (EAE). These drugs epigenetically impair antigen presentation by DCs, but whether these drugs affect ES is unknown. Here, we investigated whether short‐term treatments with these compounds would impair ES, thereby preventing EAE relapses. Experimental Approach We used a model of relapsing EAE in SJL mice and also adopted in vivo and ex vivo models of DC‐dependent T‐cell polarization. The effect of PARP‐1 inhibitors on ES was evaluated at the humoral and cellular level. Key Results Short‐term treatments with PARP‐1 inhibitors during the acute phase of relapsing EAE of mice induced, at later times, more tolerogenic DCs, increased numbers of Treg cells and impairment of ES at the humoral and cellular level. These effects are followed by long‐lasting reduction of relapse severity and incidence, although drug treatment had been discontinued for several weeks. PARP‐1 inhibitors also induced tolerogenic DCs and increased Treg cells number and function in a model of ovalbumin immunization. Conclusions and Implications Our data emphasize the therapeutic potential of PARP‐1 inhibitors in the treatment of relapsing‐remitting MS and additional ES‐driven autoimmune disorders.